PERILAKU DAN JENIS PAKAN ORANGUTAN KALIMANTAN (PONGO PYGMAEUS LINNAEUS, 1760) DL KALIMANTAN - KUNCORO, PURWO; -, SUDARYANTO; ESWARYANTI KUSUMA YUNI, LUH Puru (Jurnal Biologi Udayana; Vol 12 No 2 (2008): JURNAL BIOLOGI, 2008)
Data collection was conducted using focal animal instantaneous. The daily activity data were group based on their ethogram and was adopting "The Standard of Orangutan's collection" from Morrogh-Bernard et al. (2002). The research collected 739 hours 29 minutes of dawn to dusk observations. The daily activity was determined by activity proportion. Rehabilitated Orangutans was found to have higher proportion of social activity (79,29%) than the one of self-action activity (23,71%). The daily activity proportions consisted of 10,44% (females) and 14,13% (males) for movement, 29,01% (females) and 30,66% (males) for resting, 12,34% (females) and 4,90% (males) for social activities, 3,36% (females) and 2,49% (males) for self activities, and also 44,85% (females) and 47,82% (males) for foraging with 96 plants species and 1 termite species as food sources.
Keywords: Behaviour; Orangutans; Pongo pygmaeus; Kalimantan.